LA FLORA LIÁSICA DEL GRUPO PAMPA DE AGNIA, CHUBUT, PATAGONIA (Ameghiniana, 2013)
Fossil plants from the Pampa de Agnía Croup, from northern Chubut province, Patagonia, are described. Coniopteris meschiana, Otozamites chubutensis and O. sueroi are proposed as new species: worid-wíde distributed species as Sagenopteris rhoijoha, Otozamites hisloni and Ginkgoites ef. digitata (this last being the first cíted Ginkgoal from Argentine Liassic strata ) are also found, together with Scleropteris vincei and Otozamites ulbosaxatiiis, prevíously known from other Argentine Liassic sediments. The Pampa de Agnia Croup is composed of three formations: F. C